Men's reactions to receiving objective feedback on their weight, BMI and other health risk indicators - Craig Donnachie; Sally Wyke; Kate Hunt (BMC, 2018)
Abstract Background Receiving information about one's weight, Body Mass Index (BMI) and other indicators of health risk may prompt behaviour change. This study investigated men's reactions to receiving information on indicators of health risk prior to taking part in a men-only weight management programme, Football Fans in Training (FFIT). It also investigated the extent to which the information was reported as influencing lifestyle change and having adverse consequences. Methods We undertook a qualitative, semi-structured, telephone interview study with 28 men who took part in FFIT. We sought to interview approximately equal numbers of men who had and had not lost 5% or more of their pre-programme body weight by the end of the 12-week programme. Data were analysed thematically utilising principles of framework analysis. Results Some men were apprehensive about receiving information which confirmed their overweight/obese status, particularly those less familiar with having similar information fed back to them. The professional football setting and the people present (including other men on the programme whom they perceived to be 'like them' and the fieldwork staff) were important factors in making the men feel comfortable in an otherwise potentially threatening situation. Men who achieved greater weight loss were more likely to report being motivated by this pre-programme feedback and to perceive themselves as responsible for their current weight and health status. However, for others the information only reaffirmed what they suspected about their relatively poor health status and was insufficient to prompt behaviour change. Conclusion Undertaking measurements and receiving information on health risk indicators, such as weight or BMI, within the context of behaviour change programmes can enhance motivation for behaviour change when communicated in an empathic and non-stigmatising way, and therefore should be considered as an integral part of interventions. However, providing feedback on health risk may be insufficient to prompt behaviour change in some people and may be detrimental to those with poor body image and/or lacking personal agency to adopt lifestyle changes. It is therefore imperative that adequate support and opportunities are made available when information on weight and disease risk are fed back within research or other settings.